PSXV-20 Effects of Narasin supplementation frequency on lambs performance. (7th December 2018) - Oliveira, G; Polizel, D; Ferraz, M; Miszura, A; Bertoloni, A; Barroso, J; Martins, A; Sardinha, L; Pires, A
Abstract: Forty-four ½ Dorper x ½ Santa Inês lambs (initial BW 33.3 ± 0.59 kg) were used in a randomized block design to evaluate the effects of different supplementation frequencies of narasin on lamb′s performance. The experimental diets consisted of 95 % coastcross hay (11.2 % CP) and 5 % ground corn (DM basis), used as delivery vehicle for the narasin. The fed offer and orts were measured daily. The treatments were: N0: ground corn without narasin; N24: daily offer of narasin at 13 ppm; N48: narasin offered every 48 hours, being 26 ppm offered on the first day and ground corn without narasin on the second day (13 ppm of narasin on average); N72: narasin offered every 72 hours, being 39 ppm offered on the first day and ground corn without narasin on the second and third days. The trial lasted 105 days, divided into 5 periods of 21 days each. The lambs were weighed at the end of each period after 14 hours fasting of feed and water. All data were analyzed using the MIXED procedure of SAS and the treatments were compared through Tukey test at 5%. There was no effect on narasin intake ( P < 0.01) among treatments N24, N48 and N72 (17.6 ± 0.34 ppm). There was no treatment effect on DMI (0.81 ± 0.03 kg/d; P = 0.28). Nonetheless, lambs fed N24 and N48 had a greater ADG (N0 = 41.1 ab ; N24 = 56.9 a ; N48 = 54.9 a ; N72 = 34.9 b g/d; P = 0.03) and feed efficiency (N0 = 0.05 bc ; N24 = 0.06 ab ; N48 = 0.07 a ; N72 = 0.04 c ; P = 0.02). In summary, narasin must be offered daily or every 48 hours in order to improve the performance of lambs fed high forage diets.